PENFLURON INDUCED MORPHOLOGICAL AND HISTOLOGICAL ABNORMALITIES IN THE OVARY OF 'AAK' GRASSHOPPER, POEKILOCERUS PICTUS FAB. - MATHUR, GIRISH (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1995)
Penfluron is a highly potential insectcide which is reported to act via interfering synthesis of chitin in insects thereby causing high mortality. In the present work an attempt was made to observe its effect on the ovary of P. pictus.